The Influence of Parents Knowledge and Health Care Access to the Identification of Children with Hearing Impairment - Asti Widuri; Muhammad Pringgo Arifianto (Berkala Kedokteran, 2019)
Abstract: Early identification and access to quality habilitative services designed for children with hearing loss is the key to developing language and communication skills commensurate with the children’s cognitive abilities. Early identification will provide the opportunity for improved outcomes for thousands of children with hearing loss. Objective: To review the role of parents knowledge and health care Access to the identification of children with hearing impairment. The study design was cross-sectional, with the sample were 45 parents of children at SLB – B Karnnamanohara Yogyakarta at the nursery-child and play group. Interviewer administered a questionnaire to the parents, for evaluations of their knowledge about deaf children and health care access. After obtained the data from the each variable, then test with chi-square statistic. The significant result shown at parental knowledge (p=0,028) and health care access (p= 0,02). This means that there were significant differences between parental knowledge about speech and language development and health care access to early detection of deafness in children. Parents knowledge and health care access influenced to the identification of children with hearing impairment. Keywords: Parental knowledge, speech and language development, early detection, children with hearing loss, health care access